WATER QUALITY MONITORING SYSTEM - Gaibnazarov B.B.; Abdukarimov Sh.N.; Mahmudov M.A.; Mukhtarov A.Sh.; Abdiualiev R.M. (JOURNAL OF NEW CENTURY INNOVATIONS, 2024)
Annotation. Water quality is crucial for maintaining human health and environmental sustainability. This article examines the importance of water quality monitoring systems that utilize advanced technologies such as sensors and microcontrollers. These systems assess various parameters, including pH, turbidity, temperature, and dissolved oxygen levels. The discussion includes the technological solutions available for real-time monitoring, the operational principles of these systems, and their practical applications in urban water supply, industrial settings, and agriculture. Finally, the paper highlights the significance of integrating Internet of Things (IoT) technologies into water quality monitoring systems to enhance data collection, analysis, and response capabilities.